Increased IFN-γ production by NK and CD3+/CD56+ cells in sexually HIV-1-exposed but uninfected individuals - Montoya, Carlos Julio; Velilla, Paula Andrea; Chougnet, Claire; Landay, Alan L.; Rugeles, Maria Teresa (Clinical Immunology, 2006)
The mechanisms involved in controlling the establishment of HIV-1 infection are not fully understood. In particular, the role of innate immunity in natural resistance exhibited by individuals who are continuously exposed to HIV-1 but remain seronegative (ESN) has not been thoroughly evaluated. We determined the frequency and function of peripheral blood innate immune cells (plasmacytoid and myeloid dendritic cells, monocytes, NK cells, CD3+/CD56+ cells and invariant NKT cells) in ESN, chronically HIV-1-infected and low-risk HIV-1 seronegative individuals. ESN demonstrated a similar frequency of innate immune cells in comparison to controls and a higher frequency of dendritic cells, NK and invariant NKT cells compared to HIV-1-infected subjects. Incubation of mononuclear cells with stimulatory CpG ODN induced CD86 and CD69 up-regulation to a similar degree on innate cells from the three study groups. CpG ODN-stimulated secretion of cytokines was also similar between ESN and controls, while secretion of IFN-α was significantly decreased in HIV-1+ individuals. Importantly, expression of IFN-γ by PMA/Ionomycin-activated CD56bright NK cells and CD3+/CD56+ cells was significantly higher in ESN when compared with controls. The anti-viral effects of IFN-γ are well established, and so our results suggest that IFN-γ production by innate immune cells might be one of the multiple factors involved in controlling the establishment of sexually transmitted HIV-1 infection.